Autoimmune Diseases in Patients With Myotonic Dystrophy Type 2 - Peric, Stojan; Zlatar, Jelena; Nikolic, Luka; Ivanovic, Vukan; Pesovic, Jovan; Petrovic Djordjevic, Ivana; Sreckovic, Svetlana; Savic-Pavicevic, Dusanka; Meola, Giovanni; Rakocevic-Stojanovic, Vidosava (Frontiers in Neurology, 2022)
Introduction: Myotonic dystrophy type 2 (DM2) is a rare autosomal dominant multisystemic disease with highly variable clinical presentation. Several case reports and one cohort study suggested significant association between DM2 and autoimmune diseases (AIDs). Aim: To analyze frequency and type of AIDs in DM2 patients from the Serbian DM registry. Patients and Methods: 131 DM2 patients from 108 families were included - 62.6% females, age at DM2 onset 40.4 (13.0) years, age at entering Registry 52.0 (12.8) years, age at analysis 58.4 (12.8) years. Data were obtained from the Akhenaten, Serbian Registry for DM, as well as through the medical electronic data system. Results: At entering Registry, 35 (26.7%) of 131 DM2 patients had AIDs including Hashimoto thyroiditis (18.1%), rheumatoid arthritis, diabetes mellitus type 1, systemic lupus, Sjogren, localized scleroderma, psoriasis, celiac disease, Graves, neuromyelitis optica, myasthenia gravis, and Guillain-Barre syndrome. At the time of data analysis, two additional patients developed new AIDs, so eventually 37 (29.6%) of 125 DM2 survivors had AIDs. Antinuclear antibodies (ANA) were found in 14 (10.7%) of 63 tested patients, including 12 patients without defined corresponding AID (all in low titers – 1:40 to 1:160). Antineutrophil cytoplasmic antibodies (ANCA) were negative in all 50 tested cases. The percentage of women was significantly higher among patients with AIDs (82.9% vs. 55.2%, p<0.01). Patients with AIDs were less likely to have myopathy on electromyography (66.7% vs. 84.8%, p<0.05). Conclusion: AIDs were present in as high as 30% of DM2 patients. Thus, screening of AIDs.